Discourse of Slavery: Freedom and the Negotiation of Power and Identity in Context - Lori Lee (Transatlantica)
The construction of narratives takes place within specific contexts, including temporal, cultural, geographical, historical, ideological, and physical. The contextual creation of slave narratives and the processes of their construction and reconstruction resulted in a negotiation of power over the authentic discourse of slavery. In this essay, narratives of former U.S. slaves recorded in the 1930s and 1940s are examined to explore how context and narrative negotiate identity and power within these contexts. Particular attention is focused on how individuals talk about slavery and how their words are indicative of identity and power relations. These narratives are supplemented with additional narratives and documents written by Anglo-Americans to further highlight different perspectives of slavery, freedom, and identity.